Need assessment of a short course on educational evaluation and assessment - Roy, Goutam; Nath, Samir Ranjan (BRAC Research and Evaluation Division (RED), 2019)
The aim of this study was to explore the feasibility of a new course on educational evaluation and assessment. In-depth interviews were carried out with a checklist prepared through field trials. Number of respondents was 19, 16 from the non-government organisations and three from the government education department. Junior, mid and senior levels officials were in the sample. The findings reveal that short certificate courses are needed on educational evaluation and assessment. Both the government and non-government education officials were interested in it. Duration of the course was suggested to be of four weeks. Involvement of high officials of the ministry and the NGO leaders in the course advisory board should he considered seriously.